Antithrombotic therapy in the postacute phase of cervical artery dissection: the Italian Project on Stroke in Young Adults Cervical Artery Dissection. Issue 7 (4th May 2022) - Pezzini, Debora; Grassi, Mario; Zedde, Maria Luisa; Zini, Andrea; Bersano, Anna; Gandolfo, Carlo; Silvestrelli, Giorgio; Baracchini, Claudio; Cerrato, Paolo; Lodigiani, Corrado; Marcheselli, Simona; Paciaroni, Maurizio; et al.
Abstract : Objective: To explore the impact of antithrombotic therapy discontinuation in the postacute phase of cervical artery dissection (CeAD) on the mid-term outcome of these patients. Methods: In a cohort of consecutive patients with first-ever CeAD, enrolled in the setting of the multicentre Italian Project on Stroke in Young Adults Cervical Artery Dissection, we compared postacute (beyond 6 months since the index CeAD) outcomes between patients who discontinued antithrombotic therapy and patients who continued taking antithrombotic agents during follow-up. Primary outcome was a composite of ischaemic stroke and transient ischaemic attack. Secondary outcomes were (1) Brain ischaemia ipsilateral to the dissected vessel and (2) Recurrent CeAD. Associations with the outcome of interest were assessed by the propensity score (PS) method. Results: Of the 1390 patients whose data were available for the outcome analysis (median follow-up time in patients who did not experience outcome events, 36.0 months (25th–75th percentile, 62.0)), 201 (14.4%) discontinued antithrombotic treatment. Primary outcome occurred in 48 patients in the postacute phase of CeAD. In PS-matched samples (201 vs 201), the incidence of primary outcomes among patients taking antithrombotics was comparable with that among patients who discontinued antithrombotics during follow-up (5.0% vs 4.5%; p(log rank test)=0.526), and so was the incidence of the secondary outcomes ipsilateral brain ischaemia (4.5% vs 2.5%; p(log rank test)=0.132) and recurrent CeAD (1.0% vs 1.5%; p(log rank test)=0.798). Conclusions: Discontinuation of antithrombotic therapy in the postacute phase of CeAD does not appear to increase the risk of brain ischaemia during follow-up.